2000
DOI: 10.1210/mend.14.8.0506
|View full text |Cite
|
Sign up to set email alerts
|

CBP (CREB Binding Protein) Integrates NF-κB (Nuclear Factor-κB) and Glucocorticoid Receptor Physical Interactions and Antagonism

Abstract: Nuclear factor-kappaB (NF-kappaB) and the glucocorticoid receptor (GR) are transcription factors with opposing actions in the modulation of immune/inflammatory responses. NF-kappaB induces the expression of proinflammatory genes, while GR suppresses immune function in part by suppressing expression of the same genes. Previously, we demonstrated that physiological antagonism between NF-kappaB and GR is due to a mutual transcriptional antagonism that requires the p65 subunit of NF-kappaB and multiple domains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 40 publications
2
68
1
3
Order By: Relevance
“…Experimentally, however, it has been demonstrated that activation of GR does not affect the interaction between RelA and CBP and that a nuclear GAL4-RelA point mutant, defective in CBP recruitment, could still be functionally repressed by GR (De Bosscher et al, 2000b), arguing against a general CBPcompetition model for inhibition or RelA by GR. Instead, CBP may act as an integrator, facilitating the physical interaction between GRa and NF-kB (McKay and Cidlowski, 2000). Although GR interactions with specific coactivators are critical for direct GR target gene transactivation, they appear to be dispensable for at least certain aspects of GR-mediated transrepression of NF-kB (Wu et al, 2004).…”
Section: Nuclear Modelsmentioning
confidence: 99%
“…Experimentally, however, it has been demonstrated that activation of GR does not affect the interaction between RelA and CBP and that a nuclear GAL4-RelA point mutant, defective in CBP recruitment, could still be functionally repressed by GR (De Bosscher et al, 2000b), arguing against a general CBPcompetition model for inhibition or RelA by GR. Instead, CBP may act as an integrator, facilitating the physical interaction between GRa and NF-kB (McKay and Cidlowski, 2000). Although GR interactions with specific coactivators are critical for direct GR target gene transactivation, they appear to be dispensable for at least certain aspects of GR-mediated transrepression of NF-kB (Wu et al, 2004).…”
Section: Nuclear Modelsmentioning
confidence: 99%
“…Interaction between GR and NF-B has been shown to result in functional antagonism (13,33). The mechanism underlying this antagonism might be competition for cofactors, including CBP, as has been proposed in some studies (15,33). Based on this model of functional antagonism, we would like to propose that a high level of constitutive NF-B activation contributes to the low level of GR reporter gene activity we observed in HK-2 cells or vice versa.…”
Section: Discussionmentioning
confidence: 62%
“…In parallel, we observed a high level of constitutive NF-B activation in non-stimulated HK-2 cells compared with A549 cells. Interaction between GR and NF-B has been shown to result in functional antagonism (13,33). The mechanism underlying this antagonism might be competition for cofactors, including CBP, as has been proposed in some studies (15,33).…”
Section: Discussionmentioning
confidence: 97%
“…A few mechanisms have been suggested for inhibition. One of these, the direct protein-protein interaction between NF-kB and GRs, is important for the mutual transcriptional antagonism between NF-kB and GRs or the cross-repression of the cAMP response element binding protein (CREBP) [67] and the catalytic protein kinase A subunit [68]. Glucocorticoids inhibit transcriptional up-regulation of T cell-derived cytokines, such as IL1-2, IL-4, IL-10, and g-interferon (1-3), and proinflammatory cytokines, such as IL-1, granulocyte-macrophage colonystimulating factor, and tumor necrosis factor-α [69,70].…”
Section: Arachidonic Acid Metabolism In the Eyementioning
confidence: 99%